2021
DOI: 10.1111/febs.15809
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and humanization of single‐domain antibodies

Abstract: receptor 1; VEGF, vascular endothelial growth factor; V H , variable heavy chain domain; V L , variable light chain domain; V H H, autonomous variable domain of camelid heavy chain-only antibody; V NAR , autonomous variable domain of shark Ig new antigen receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 140 publications
0
72
0
Order By: Relevance
“…Inspired by the FDA approval of the first Nb therapy (Morrison, 2019), a number of preclinical and clinical programs have been initiated, providing critical insights into the safety profiles, dosing regime, and efficacy of therapeutic Nbs. For example, recent studies based on dozens of preclinical results found that ADA responses were minor and were generally non-neutralizing to compromise efficacy (Rossotti et al, 2021). Clinical trials have further revealed limited safety issues of Nbs (mostly humanized Nbs) in both patients and healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…Inspired by the FDA approval of the first Nb therapy (Morrison, 2019), a number of preclinical and clinical programs have been initiated, providing critical insights into the safety profiles, dosing regime, and efficacy of therapeutic Nbs. For example, recent studies based on dozens of preclinical results found that ADA responses were minor and were generally non-neutralizing to compromise efficacy (Rossotti et al, 2021). Clinical trials have further revealed limited safety issues of Nbs (mostly humanized Nbs) in both patients and healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“… 44 The ACE2 ECD was fused to either the N- or C-terminus of the Fc while the anti-pIgR VHH moieties were formatted only on the N-terminus of the bifunctional molecules to avoid binding with preformed antibodies in human sera. 45 All molecules featured a human IgG1-based constant region.…”
Section: Resultsmentioning
confidence: 99%
“…However, camelid antibodies have been reported to share greater sequence similarity with human antibodies than with antibodies from other commonly immunized species, such as mice. [ 47 ] While immunogenicity of nanobodies is difficult to predict and direct analysis is beyond the scope of this study, nanobodies have been successfully humanized and administered as therapeutics. The first therapeutic nanobody, caplacizumab, was approved by the FDA in 2019, [ 48 ] demonstrating the potential of nanobodies in therapeutic applications.…”
Section: Discussionmentioning
confidence: 99%